1980
DOI: 10.1038/clpt.1980.236
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of lipolysis by nicotinic acid and by acipimox

Abstract: Acipimox (5-methylpyrazinecarboxylic acid 4-oxide) is a new lipolysis inhibitor that has a distant chemical relationship with nicotinic acid (NA). The tritiated compound (100 mg) is rapidly absorbed, peak plasma radioactivity being reached after 2 hr, with an almost total elimination unchanged in urine. A comparison of th antilipolytic activity of three doses of acipimox and three doses of NA showed acipimox to be 20 times as potent as NA. There was a correlation between intensity and duration of effect for ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(45 citation statements)
references
References 0 publications
1
44
0
Order By: Relevance
“…Several pharmaceutical companies began developing selective agonists of GPR109A (42)(43)(44)(45)(46)(47). Walters et al ( 48 ) suggested that the effects of niacin on FFAs and fl ushing could be segregated.…”
Section: Niacin Receptormentioning
confidence: 99%
“…Several pharmaceutical companies began developing selective agonists of GPR109A (42)(43)(44)(45)(46)(47). Walters et al ( 48 ) suggested that the effects of niacin on FFAs and fl ushing could be segregated.…”
Section: Niacin Receptormentioning
confidence: 99%
“…Following an experimental protocol, previously designed by our group to investigate the interplay GH/FFA in normal subjects (27,28), the first eight acromegalic subjects (group 1 of Table 1) received (per os, on two different days, at a 3 day-interval, and in a random order) placebo or 250 mg acipimox (Olbetam, Pharmacia & Upjohn, Inc., Milan, Italy) at 0700 h and at 1100 h. Acipimox is an inhibitor of lipolysis analogous to nicotinic acid that is known to act only on the adipose tissue (32,33). In both tests, GHRH (1-29 NH 2 ), 50 g iv, was administered at 1300 h.…”
Section: Subjects and Experimental Proceduresmentioning
confidence: 99%
“…Nicotinic acid reduces lipolysis in adipose tissue and inhibits the release of fatty acids into the circulation (29). Less fatty acids therefore reach the liver for synthesis of VLDL and subsequently LDL.…”
Section: Nicotinic Acid a N D Derivativesmentioning
confidence: 99%
“…It is often fortuitous that many patients who require these drugs are already on low-dose aspirin for vascular disease. Acipimox also seems to be more potent than nicotinic acid in suppressing fatty acid release (29), although less effective in reducing LDL-cholesterol (30).…”
Section: Nicotinic Acid a N D Derivativesmentioning
confidence: 99%